SENGKETA HASIL PEMILIHAN BUPATI DAN WAKIL BUPATI LABUHANBATU SELATAN (STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 37/PHP.BUP-XIX/2021: Dispute On South Labuhanbatu Regent Election Result (Study Of Constitutional Court Ruling No. 37/Php.Bup-Xix/2021) - Muhammad Faishal; Radian Syam (Reformasi Hukum Trisakti, 2024)
When elections are held, conflicts often arise as a result of the elections. This conflict arose during the regional elections for the regent and deputy regent of South Labuhanbatu in 2020 due to fraud which resulted in differences in votes at a number of polling stations. The main issue discussed was whether the re-voting in the election for the Regent and Deputy Regent of South Labuhanbatu was in accordance with the contents of Constitutional Court Decision Number 37/PHP. BUP-XIX/2021 and what legal impacts will arise as a result of the re-voting. This research uses descriptive normative legal research methods. The data used consists of primary and secondary data which are analyzed qualitatively, and conclusions are obtained through deductive logic. The results and conclusions show that the re-voting carried out in 16 villages by the KPU of South Labuhanbatu Regency was in accordance with the ruling of the Constitutional Court. The legal impact that arises from repetition of votes is when an applicant who previously submitted a request does not resubmit his application to the Constitutional Court. As a result, the KPU of South Labuhanbatu Province approved the elected candidates for Regent and Deputy Regent of South Labuhanbatu for 2020